2023
DOI: 10.1007/s00535-023-02031-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity in response to food images in patients with irritable bowel syndrome and functional dyspepsia

Ryo Katsumata,
Takayuki Hosokawa,
Noriaki Manabe
et al.

Abstract: Background Functional dyspepsia (FD) and irritable bowel syndrome (IBS) are caused and exacerbated by consumption of fatty foods. However, no study has evaluated brain activity in response to food images in patients with disorders of gut–brain interaction (DGBI). This study aimed to compare food preference and brain activity when viewing food images between patients with DGBI and healthy controls. Methods FD and IBS were diagnosed using the ROME IV criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The experimental procedure was similar to that described in a previous study [ 6 ]. Briefly, the participants were instructed to sit on a chair in a quiet room facing a laptop computer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental procedure was similar to that described in a previous study [ 6 ]. Briefly, the participants were instructed to sit on a chair in a quiet room facing a laptop computer.…”
Section: Methodsmentioning
confidence: 99%
“…Fatty food intake reportedly induced gastrointestinal (GI) symptoms in patients with FD and those with IBS [ 4 , 5 ]. Additionally, our previous study showed that preference scores for fatty food images were significantly lower in patients with DGBI, particularly those with FD [ 6 ]. Regarding brain activity in patients with DGBIs, previous studies have reported alterations in several brain regions in patients with FD and those with IBS when compared to healthy controls [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, patients need simply sit on a chair in a relaxed manner and perform a series of tasks or tests guided by computer instructions. One study showed that patients with functional dyspepsia exhibited increased activation in the DPC in response to fatty food images, and they also reported that these images reminded them of uncomfortable abdominal symptoms, such as abdominal pain and fullness (Katsumata et al., 2023). This suggests that high‐fat food clues can affect brain areas involved in emotional inhibition and memory processing, which are governed by the prefrontal cortex.…”
Section: Neuroimaging Technologies For Food Sensory and Consumer Rese...mentioning
confidence: 99%
“…The consumer sensory perception is a complicated experience that is influenced by the differentiation of food attributes (e.g., brand, label, packaging, sensory and physical characteristics), individual factors (e.g., cultural background, age, dietary pattern, and emotional state), and background variations (e.g., eating with familiar or unfamiliar individuals, dining at home or restaurant) (de Wijk et al., 2019; Katsumata et al., 2023; Machín et al., 2023; Mena et al., 2023; Nath et al., 2020; Pichierri et al., 2021; Semenova et al., 2023; Spinelli & Jaeger, 2019; Wang, Zhang, et al., 2022; Xu et al., 2022). There exist two directions used to elucidate human sensory perception of food (shown in Figure 1).…”
Section: Introductionmentioning
confidence: 99%